2015
DOI: 10.3989/gya.1313143
|View full text |Cite
|
Sign up to set email alerts
|

Rheological properties and physical stability of ecological emulsions stabilized by a surfactant derived from cocoa oil and high pressure homogenization

Abstract: SUMMARY:The goal of this work was to investigate the influence of the emulsification method on the rheological properties, droplet size distribution and physical stability of O/W green emulsions formulated with an eco-friendly surfactant derived from cocoa oil. The methodology used can be applied to other emulsions. Polyoxyethylene glycerol esters are non-ionic surfactants obtained from a renewable source which fulfill the environmental and toxicological requirements to be used as eco-friendly emulsifying agen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…Interestingly, both emulsions stabilized with BM cellulose demonstrated the occurrence of hysteresis (data not shown) within the range of shear rate investigated, suggesting significant instability during shearing. The viscosity of HPH-NC and HPH-TP emulsions showed the typical non-Newtonian shear thinning behavior, which is markedly different from the Newtonian behavior observed for surfactant-stabilized emulsions [34]. The decrease in viscosity can be linked to the breakdown of the entangled network of nanofiber bundles and their orientation along flow lines upon the shear force application [35].…”
Section: Characterization Of Nanocellulose-stabilized Pickering Emulsionsmentioning
confidence: 83%
“…Interestingly, both emulsions stabilized with BM cellulose demonstrated the occurrence of hysteresis (data not shown) within the range of shear rate investigated, suggesting significant instability during shearing. The viscosity of HPH-NC and HPH-TP emulsions showed the typical non-Newtonian shear thinning behavior, which is markedly different from the Newtonian behavior observed for surfactant-stabilized emulsions [34]. The decrease in viscosity can be linked to the breakdown of the entangled network of nanofiber bundles and their orientation along flow lines upon the shear force application [35].…”
Section: Characterization Of Nanocellulose-stabilized Pickering Emulsionsmentioning
confidence: 83%
“…The phase separation causes ruptures of the membrane due to gravity and colloidal and mechanical forces and, for this reason, expresses the sensitivity to fusion. Trujillo-Cayado et al (2015) studied the stability properties of microemulsions (O/W) of cocoa oil in different proportions by high-pressure homogenization. The authors reported values of separation phases in a range of 6-8% and particle sizes of 1-10 lm after 33 days.…”
Section: Discussionmentioning
confidence: 99%
“…It is possible to find a relation between K and n values. K results, for samples with different n values, may be properly compared since a modified Ostwald de Waele equation is used [6,60,62,64,65].…”
Section: Rheological Modelingmentioning
confidence: 99%